Online tutoring system in college : case study in university college Shahputra - Rafidah binti Mohd Arif (Kulliyah of Engineering, International Islamic University Malaysia, 2013)
Online tutoring system is one of the approaches using in today's private education which allows the tutors and students to communicate each other in a real time. However, some of private college is still done the learning process inside the classroom with a large number of students. Online tutoring system with objective to upgrade the conventional system to computer oriented learning to students of Diploma in Computer Science Multimedia (DCSM) at University College Shahputra (UCSA). This method makes the learning process more comfortable and efficient. System development life cycle (SDLC) combine with prototyping technique is used for the development process. The methodology is choose because it attempts to reduce inherent project risk by breaking a project into smaller segments, provides easy to change during the development process and it is suitable used on developing online system. A survey had been done among lecturer of DCSM to identify the problems while the students learn in conventional way to find the better solution to the future's students. The complete system contain with a lot of tools for the convenience of students and lecturers. The major tools include are the learning materials, bulletin and learning assessment such as quizzes and assignments. Students have been tested on using the system with taking the quiz while the lecturer are been used the system on developing the set of learning materials. The system testing is focusing on acceptance testing to determine if the requirements of the specification system are met. The findings show the online tutoring system was interesting and pleasant to use. The students agree the online learning give them a flexibility on their learning compared to traditional learning. As the conclusion, students satisfied with the content, structure and had a motivation on using online tutoring system.